The Dixa inextricata Dyar & Shannon (Diptera: Dixidae) species group, with two new cryptic species from the eastern Nearctic Region - Moulton, John K. (Zootaxa, 2016)
Dixa inextricata Dyar & Shannon is currently regarded as a widespread species in the eastern Nearctic, currently distinguished from sympatric congeners by its brown coloration and triangular gonostylus as seen in lateral view. Recent morphological examination of archival material and dual morphological and molecular examination of recently acquired material fitting the diagnosis of Dixa inextricata revealed the presence of three species. These three species have never been found occupying the same stream in spite of two different pairs of members being geographically and temporally sympatric. The diagnosis of D. inextricata is revised, two closely related species D. appalachiensis sp. nov. and D. calciphila sp. nov., are described and the D. inextricata species group is defined. A key to separate males and natural history data for each species are provided.